Application of Persuasion Through Costumer Purchase Decision in Linnect Marketing Program - Jauhar, Lutfiana Musleh; Marsasi, Endy Gunanto (Jurnal Ecogen, 2024)
In the current era, the Internet and marketing in a business have become the backbone of the world economy; the Internet has proven to be an effective marketing tool for many different sectors. The decline in unwilling and inactive customers in 2021, namely 17,282, which is 18.54%, proves that telemarketing needs to be improved. This study aims to identify the effect of marketing through telemarketing at PT Telkom Witel Yogyakarta on customers to improve services amid consumer needs. This research method uses descriptive qualitative methods, with data collection techniques by interview. The results of this study indicate that the proposed "LINNECT" program at PT Telkom Witel Yogyakarta can improve marketing services by presenting product information on one website. This program utilizes the theory of persuasion, the concept of consumer purchasing decisions, to influence behavior. Telkom hopes this program can increase customer satisfaction and achieve target points with attractive rewards. The practical implication is the positive contribution to the Company and customer relationship and the proposed program to improve service quality and sales.